PENGARUH TINGKAT BAGI HASIL, SUKU BUNGA DEPOSITO UMUM, INFLASI, UKURAN BANK UMUM SYARIAH, DAN LIKUIDITAS TERHADAP DEPOSITO MUDHARABAH PADA BANK UMUM SYARIAH DI INDONESIA - Rini Husniwati, 13.05.52.0144; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2017)
This study aimed to examine and analyze the effect of level of profit sharing, deposit interest rates, inflation, the size of the bank, and liquidity of mudharabah deposits at Islamic commercial bank and to know the value of the coefficient of each Islamic Commercial Bank. The population in this study is the Islamic Commercial Bank listed on the OJK website during January to December 2014. Monthly financial statements of Islamic Commercial Bank obtained from the OJK website, deposit interest rates obtained from SEKI website and inflation obtained from BI website.The sampling method using purposive sampling. The sample in this study a number of 114. The method used is the Panel Data Regression. The results showed that the level of profit sharing and the size of the banks positive and significant effect on mudharabah deposits. Deposit interest rates, inflation and FDRnegative and not significant effect on the mudharabah deposits. The highest coefficient value is Bank Muamalat IndonesiaKeywords: Level of Profit Sharing, Deposit Interest Rates, Inflation, Bank Size, Liquidity and Mudharabah Deposit